Buffer funding of unemployment insurance in a dynamic labour union model - Marja-Liisa Halko (Bank of Finland, 2003)
In this paper we study the implications of the unemployment insurance (UI) financing system on wage levels and employment when labour markets are unionised and the revenues of the firms are stochastic.We use the basic monopoly union approach of wage and employment determination and assume that unemployment benefits are financed by employees UI contributions to the union s UI fund and by the government s tax revenue.The main focus of this paper is on the effects of UI buffer funding on employment fluctuations.We show that, compared with the pay-as-you-go financing system, buffer funding stabilises the economy by decreasing employment fluctuations where wages are flexible.If wages are rigid, buffer funding stabilises net wage variations, but has hardly any effect on employment fluctuations.
URN:NBN:fi:bof-20140807165
Keywords: E61; J51; J65; 330; unemployment insurance; unions; stabilisation; buffer funding